Modernization of hydroponic farming using rice husk for community food security in Karang Langit, Lamongan - Pujiastuti, Caecilia; Muchamad, Raka Selaksa Charisma; Rohmah, Aisyah Alifatul Zahidah; Chakim, M. Ghufron; Fajrin, Alifah Nur Aini; Rizal, Achmad; Azka, Salsabilla (Community Empowerment, 2025)
Rice husk waste is an abundant agricultural byproduct in Karang Langit Village, Lamongan, but its utilization is still limited, posing a potential environmental problem. This community service program aims to modernize agricultural practices by utilizing rice husk as a hydroponic growing medium to support food security and promote a circular economy. The methods applied include community coordination, carbonization of rice husks, preparation of the hydroponic system, and both theoretical and practical hands-on training. Evaluation results show a significant increase in participants’ knowledge by 32%. A total of 85% of participants successfully prepared a viable rice-husk-based growing medium, and 75% were able to cultivate and harvest leafy vegetables in the trial phase. Additionally, a farmer group was formed and is committed to independently continuing hydroponic practices after the program’s conclusion. These results confirm that utilizing rice husk as a hydroponic medium not only enhances community skills and self-sufficiency but also opens new economic opportunities. This model is recommended for replication in other agricultural areas to support local food security and environmental sustainability.